Community intervention to increase seafood consumption (CIISC) - McManus, Alexandra; White, James; Newton, Wendy; Storey, Jessica; McManus, Jennifer; Cuesta-Briand, B.; Golightly, A. (Centre of Excellence for Science, Seafood and Health, Curtin Health Innovation Research Institute, Curtin University, 2011)
In summary, this report describes a whole of community intervention aimed at increasing consumption of seafood. The health benefits of seafood were reviewed and a suit of communication materials developed including: primary and secondary education models. vocational eductaion materials, resources for general practitioners and point of sale materials. Evaluation of project outcomes revealed an increase in seafood consumption during and one month after the intervention period.